Short supply food chains in rural development - A. I. Kostyaev; E. A. Shepeleva (Аграрная наука Евро-Северо-Востока, 2019)
The article presents the results of study of the possibilities and prerequisites for the development of rural territories based on the restructuring of the agri-food system at the local level. The inclusion of peasant farm enterprises, private subsidiary farms, agricultural consumer cooperatives and agricultural cooperative markets into short supply food chains has been observed. The study was conducted on the basis of Rosstat data across the subjects of the Russian Federation. The polling survey was carried out in Vologda, Leningrad and Novgorod regions. The methods of correlation and socio-economic analysis were used. Groups of regions with a high share (60-70%; 71-80%; > 80%) of peasant farms and private subsidiary farms in food production as territories with prerequisites for the formation of short supply food chains were identified. The tendencies of decreasing the number of agricultural consumer cooperatives and their localization in a limited number of regions have been established. In ten regions of Russia 52.6% of agricultural consumer cooperatives are concentrated and 49.2% of peasant farms as their members are located. Cooperatives in Russia as a whole cover only 5.2% of all peasant farms. Operating agricultural consumer cooperatives provide their services only to 4% of private subsidiary farms. Based on the correlation of Spearman's ranks, a moderate tightness of the direct relationship between the number of agricultural consumer cooperatives and the number of peasant farms - members of the agricultural consumer cooperatives (correlation coefficient is 0.56) and a weak relationship between the number of agricultural consumer cooperatives and the number of private subsidiary farms served by them (0.08) has been established. It is concluded that agricultural consumer cooperatives can have a significant impact on the formation of short supply food chains only in certain regions with a developed cooperative network. The results of the questionnaire of agricultural consumer cooperatives have revealed a number of interrelated problems concerning the sale of products, the need for the development of agricultural cooperative markets and other retail markets. It was proposed to manage markets and food chains in general on the basis of a corporate social responsibility model using rural web networks (Rural web).Conflict of interest: the authors stated that there was no conflict of interest.